PERSEPSI GURU MADRASAH IBTIDAIYAH TERHADAP PENYELENGGARAAN PENDIDIKAN INKLUSI - Siti Habsari Pratiwi; Wahyuni, Wahyuni (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The implementation of inclusive education is the main highlight of the government's efforts to improve the quality of Indonesian education. His belief is that all students, without exception, should benefit from high-quality learning and enjoy full participation in the education system. This study aims to determine the perception of Madrasah Ibtidaiyah teachers towards the discourse on the implementation of inclusive education. This research is qualitative with an investigative approach. This study involved 13 existing Madrasah Ibtidaiyah teachers in one of Indonesia's westernmost provinces who were randomly selected. The results show that teachers are still confused with the definition of inclusive education, which causes disorientation in the implementation of inclusive education. As a result of such disorientation, (1) teachers are embarrassed to mention that there are children in their schools or classes; (2) the teacher's excessive anxiety in the implementation of learning in the classroom, such as bullying; (3) the teacher's incorrect orientation of learning outcomes; and (4) discrimination against children. To avoid disorientation in the implementation of inclusive education, it is very important to provide special training for madrasah teachers on topics such as designing lessons, determining learning models, developing learning media, the assessment process in inclusive classes, and the governance and management of inclusive education.